2021
DOI: 10.1101/2021.10.30.21265694
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative genomics and characterization of SARS-CoV-2 P.1 (Gamma) Variant of Concern (VOC) from Amazonas, Brazil

Abstract: BackgroundP.1 lineage (Gamma) was first described in the State of Amazonas, northern Brazil, in the end of 2020, and has emerged as a very important variant of concern (VOC) of SARS-CoV-2 worldwide. P.1 has been linked to increased infectivity, higher mortality and immune evasion, leading to reinfections and potentially reduced efficacy of vaccines and neutralizing antibodies.MethodsThe samples of 276 patients from the State of Amazonas were sent to a central referral laboratory for sequencing by gold standard… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…As for the antibody treatment in clinical use, the cocktail consisting of LY-CoV555 (also known as Bamlanivimab) and LY-CoV016 (also known as Etesevimab) has been authorized for emergency use. Previous studies have revealed that the mutations at 484 and 417 positions of the spike are associated with immune evasion 22 and that both Beta and Gamma variants could escape the neutralization of LY-CoV555 (due to E484K) and LY-CoV016 (due to K417N/T). 23 Since the Omicron variant also contains E484A and K417N mutations, it is likely that Omicron would also resist these two antibodies.…”
Section: Characteristics Of Omicron Variantmentioning
confidence: 99%
“…As for the antibody treatment in clinical use, the cocktail consisting of LY-CoV555 (also known as Bamlanivimab) and LY-CoV016 (also known as Etesevimab) has been authorized for emergency use. Previous studies have revealed that the mutations at 484 and 417 positions of the spike are associated with immune evasion 22 and that both Beta and Gamma variants could escape the neutralization of LY-CoV555 (due to E484K) and LY-CoV016 (due to K417N/T). 23 Since the Omicron variant also contains E484A and K417N mutations, it is likely that Omicron would also resist these two antibodies.…”
Section: Characteristics Of Omicron Variantmentioning
confidence: 99%
“…Is more likely to occur in P.1 (18.2%) [108], but globally the deletion (NSP6:S106/G107/F108del) is more common in this position. According to GISAID (as on 1 September 2021), this deletion is found in 97.21% of the sequences [109].…”
Section: Non-spike Mutationsmentioning
confidence: 99%
“…Is more likely to occur in P.1 (18.2%) [108], but globally the deletion (NSP6:S106/G107/F108del) is more common in this position. According to GISAID (as on 1 September 2021), this deletion is found in 97.21% of the sequences [109]. Sun et al suggested that this mutation may affect viral shedding and hence transmissibility, thereby altering viral load [110].…”
Section: Mutations In Nsp5mentioning
confidence: 99%
“…1.351 (Beta) in South Africa (December 2020) (4), P.1 (Gamma) in Brazil (January 2021) (5), and the B.1.617 (Delta) variant in India (January 2021) (6). It is notably evident that the mortality rate due to the COVID-19 disease surged in the countries where the newer variants were discovered (7)(8)(9)(10). The B.1.1.7 (Alpha) variant has been linked with an increased risk of transmissibility, hospitalization, and death (8,(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%